Genesis of the Selinsing gold deposit, Peninsular Malaysia: Constraints from mineralogy, geochemistry and in situ sulfur isotope compositions of sulfides - Sun, Chao; Yang, Xiaoyong; Du, Gaofeng; Abdul Aziz, Jasmi Hafiz (Elsevier, 2019)
As a renowned orogenic lode gold deposit, the Selinsing gold deposit is located in the Central Belt of Peninsular Malaysia. Geologically, the gold deposit is characterized by auriferous quartz veins and fine-grained gold minerals coexisted with sulfides, and the ore body is hosted by low-grade metamorphic sedimentary rocks and volcanic rocks. Furthermore, gold mineralization is closely related to tectonic deformation. Four main stages of vein formation have been identified, namely, (1) quartz-pyrite-arsenopyrite vein, (2) quartz-pyrite-gold vein, (3) quartz-stibnite-pyrite vein, and (4) quartz-chlorite vein. The occurrence of gold includes two types, i.e., visible gold and invisible gold. The former is featured by coarse-grained gold (millimeter-scale, such as auriferous quartz veins) and fine-grained gold (micron-scale, such as native gold, calaverite, and electrum), the latter is contained in pyrite and arsenopyrite in the form of nano-scale native gold particles (Au0) and lattice gold (Au1+). The geothermometer of arsenopyrite and chlorite as well as temperature-sulfur fugacity diagram indicate that the temperature and sulfur fugacity of hydrothermal fluid decrease gradually. Considering that the sulfur fugacity drops gradually and aqueous inclusions coexist with carbonic inclusions, it is inferred that sulfuration reaction in which sulfur is consumed to produce sulfides and fluid immiscibility or phase separation may be responsible for gold precipitation. Tested by LA-MC-ICP-MS, the in-situ sulfur isotope compositions of sulfides formed in different stages are homogenous (about −1 to 1‰) and the calculated H2S-dominated hydrothermal fluid is also consistent (about −2 to 0‰) in sulfur isotope compositions, which reflect the mantle or ultrabasic rock and basic rock or magmatic rocks may be a potential source of sulfur. Combined with possible source and tectonic evolution of Peninsular Malaysia, possible metallogenic processes are proposed to explain genesis of the Selinsing gold deposit and other gold deposits in the Central Belt, i.e., ore-forming fluid was differentiated from oceanic crust and/or fertilized mantle wedge, or ore-forming fluid may be sourced from concealed magmatic rocks that formed by subduction of the Palaeo-Tethys toward the East Malaysia block. © 2019 Elsevier B.V.